THE EFFECTIVENESS OF EDRAW MIND MAP APPLICATION IN TEACHING WRITING OF RECOUNT TEXT AT THE TENTH GRADE OF MAN 4 KEDIRI - Pujiana, Siti (Jurnal Pendidikan Bahasa Inggris Proficiency, 2020)
The objectives of this study were (1) to describe the student’s skill of recount text in an experimental class taught by using Edraw Mind Map, (2) to describe the students’ skill of control class without being taught Edraw Mind Map, and (3) to investigate whether there is a significance in teaching writing skill of recount text between experimental and control class at tenth grade of MAN 4 Kediri. During the research quantitative approach of true experimental was used as the research design. This research used two classes which became experimental class (X Social Science Program 1) which was taught by using Edraw Mind Map Application and control class (X Natural Science Program 4) which was not taught by using Edraw Mind Map Application. The population was the first year students of MAN 4 in academic year of 2019/2020. Out of this population, 60 students were taken as sample. There were two classes, each of which consisted of 30 students. The data were collected by using writing test and questioners.